Index of contamination/pollution factor, geo-accumulation and ecological risk in ex-gold mining soil contaminated with mercury - Amsar Maulana; Mimien Harianti; Teguh Budi Prasetyo; Herviyanti Herviyanti (Journal of Degraded and Mining Lands Management, 2023)
Mercury is a hazardous contaminant, and it is necessary to clean up Hg contamination on an ongoing basis. However, Hg contamination and ecological risks have not become a particular concern in the community. As a first step, this study evaluated the environmental risk assessment of Hg contamination/pollution in ex-gold mining soil. The results showed that the average total Hg in ex-gold mining soil was 4.11 and 4.25 mg kg-1 for depths 0-20 and 20-40 cm, respectively, greater than the threshold limit set nationally (0.3 mg kg-1) and internationally (0.05-1 mg kg-1). The index of contamination/pollution factor and geo-accumulation of Hg were 13.70 and 1.39 at a depth of 0-20 cm, and 14.16 and 1.47 at a depth of 20-40 cm. The prospective ecological risk index and risk quotient were 5.48E2 and 1.03E2 at a depth of 0-20 cm, and 5.66E2 and 1.06E2 at a depth of 20-40 cm. The contamination/ pollution factor and ecological risk index indicate high Hg contamination and pollution in the soil. Therefore, appropriate technology is needed for the remediation process of ex-gold mining soil that considers all elements to a user-friendly level, such as amelioration technology with heavy metal inactivation techniques.